Early Decompressive Laparotomy for Intra-Abdominal Hypertension Following Initiation of Venovenous Extracorporeal Membrane Oxygenation. Issue 5 (May 2020) - Boulos, Francesca M.; Pasrija, Chetan; DiChiacchio, Laura; Rouse, Michael; Raithel, Maxwell; Mackowick, Kristen; Rector, Raymond; Mazzeffi, Michael A.; Griffith, Bartley P.; Diaz, Jose J.; Kon, Zachary N.; Deatrick, Kristopher B.
Abstract : Patients supported with venovenous extracorporeal membrane oxygenation are at risk for intra-abdominal hypertension and abdominal compartment syndrome. Flow through the return cannula may be compromised in these patients, resulting in inadequate support and end-organ malperfusion. Early decompressive laparotomy can mitigate these complications and potentially improve outcomes. Here we review a series of nine patients undergoing early decompressive laparotomy for abdominal compartment syndrome at a single institution and propose an algorithmic approach to the management of these patients.